2021
DOI: 10.1021/acsapm.1c00096
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Metal–Organic Framework/Polymer Composites via a One-Pot Solvent Crystal Template Strategy

Abstract: Metal–organic framework (MOF)/polymer composites combining advantages of both materials have received significant attention in the recent years. However, the complexity and inefficiency of the current fabrication approaches have hindered their further development. Herein, we demonstrate a facile one-pot solvent crystal template strategy to efficiently fabricate ZIF-8/polyurethane (PU) composites. This method eliminated the pre-synthesis and purification of MOFs, thus greatly simplifying the fabrication process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…As shown in the Fig. 4b, BC/PU-5 foam composites had selective adsorption on these OSs, which may be due to the fact that the density and viscosity of the solvent itself had a significant impact on the adsorption efficiency (Chen et al 2021). The results showed that BC/PU foam composites exhibited excellent adsorption properties for these OSs, among which the adsorption capacities of n-hexane, chlorobenzene and 1,2-dichloroethane were 23.6 g g −1 , 18.1 g g −1 and 16.5 g −1 , respectively.…”
Section: Oss Adsorption Behaviormentioning
confidence: 88%
“…As shown in the Fig. 4b, BC/PU-5 foam composites had selective adsorption on these OSs, which may be due to the fact that the density and viscosity of the solvent itself had a significant impact on the adsorption efficiency (Chen et al 2021). The results showed that BC/PU foam composites exhibited excellent adsorption properties for these OSs, among which the adsorption capacities of n-hexane, chlorobenzene and 1,2-dichloroethane were 23.6 g g −1 , 18.1 g g −1 and 16.5 g −1 , respectively.…”
Section: Oss Adsorption Behaviormentioning
confidence: 88%
“…354 and 355. Furthermore, other polymers have also been studied, such as rubber, 356 polydopamine, 357,358 acrylic acid, 359,360 polytetrafluoroethylene (PTFE), 361,362 cyclic olefin copolymer (COC), 363 polyvinyl alcohol (PVA), 364 GCE and polylactic acid (PLA), 365 polypropylene, 366,367 polyvinyl chloride, 368 poly (sodium 4-styrenesulfonate), 369 poly(MMA- co -EDMA) membranes, methyl methacrylate (MMA) and ethylene glycol dimethacrylate (EDMA), 370 polyurethane, 371 polyethylenimine, 372 and aerogels. 373…”
Section: Insulator Substratesmentioning
confidence: 99%